The problem with provisionals [patents]. - Teska, K.
A patent based on a poorly written provisional application may prove worthless. First allowed in the United States in 1995, provisionals have been touted as convenient vehicles for achieving patent-pending status. With a provisional filed, the invention can be disclosed or sold without fear of losing patent rights so long as a full utility patent application is filed within a year of the provisional. But the provisional must have one crucial element: it must cover all the claims made in the final, utility application. The description of how the invention is made and used must include enough detail for others to duplicate the invention after the patent expires. But if someone challenges the patent, and the written description in the provisional is found inadequate, all could be lost. This article briefly describes a case study to show the problems that can be encountered with provisionals.
Keywords: Claims; Full utility patent application; Patent-pending status; Provisional patents